User innovation and the entrepreneurship phenomenon in the digital economy - Isaías, Pedro; Carvalho, Luísa Cagica 1970- (IGI Global, Disseminator of Knowledge, 2018)
"This book addresses the strategic business practice and the role of end-users' issues within the digital economy. It emphasizes emergent and innovative aspects of design, development and implementation of digital economy initiatives, highlighting the relationship and interaction between humans and the technologies they routinely use to operate and live in a digital economy"--
Includes index
Keywords: Strategic planning; Entrepreneurship; Electronic commerce; Internet in public administration; Internet in education